2014
DOI: 10.1080/00224499.2014.910745
|View full text |Cite
|
Sign up to set email alerts
|

Hooking Up and Psychological Well-Being in College Students: Short-Term Prospective Links Across Different Hookup Definitions

Abstract: Hooking up (sex outside committed, romantic relationships) is feared to result from or lead to compromised psychological well-being among undergraduates, yet longitudinal evidence is scarce and inconclusive, and different hookup definitions complicate cross-study comparisons. This study examined short-term longitudinal associations with four well-being indicators (depression, anxiety, life satisfaction, and self-esteem) across several definitions of hookups based on relationship length (one time, longer casual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…Among young adults, a similar result of no association between self-esteem and engagement in CSREs was found over a few months (Fielder & Carey, 2010;Vrangalova, 2015a). The relationship between self-esteem and sexual behaviors among adolescents, including the initiation of sexual intercourse as well as CSREs, appears to be complex.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Among young adults, a similar result of no association between self-esteem and engagement in CSREs was found over a few months (Fielder & Carey, 2010;Vrangalova, 2015a). The relationship between self-esteem and sexual behaviors among adolescents, including the initiation of sexual intercourse as well as CSREs, appears to be complex.…”
Section: Discussionsupporting
confidence: 53%
“…Higher self-esteem has been reported as a predictor of fewer CSREs involving oral sex among young women (Fielder et al, 2013). Nevertheless, other studies have found no predictive role of self-esteem on CSREs among women or men (Fielder & Carey, 2010;Vrangalova, 2015a). Conclusions based on convergent findings are impossible to draw regarding whether higher or lower self-esteem is linked to a greater likelihood of engaging in CSREs among young adults and among adolescents, as there are no available prospective studies.…”
Section: Psychological Well-being and Casual Sex Relationships And Exmentioning
confidence: 44%
See 2 more Smart Citations
“…We also found that dissatisfaction with sexual life is related to sociosexual desire but not to past behavior or to attitudes. Even so, further research in this field is necessary to examine the antecedents of sociosexuality and their possible role as mediators between casual sex and its consequences (Owen, Fincham, & Moore, 2011;Vrangalova, 2015;Vrangalova & Ong, 2014).…”
Section: Discussionmentioning
confidence: 99%